Microtubule dynamics in vivo: a test of mechanisms of turnover. - Paul J. Sammak; Gary J. Gorbsky; Gary G. Borisy (1987)
Clarification of the mechanism of microtubule dynamics requires an analysis of the microtubule pattern at two time points in the same cell with single fiber resolution. Single microtubule resolution was obtained by microinjection of haptenized tubulin (fluorescein-tubulin) and subsequent indirect immunofluorescence with an antifluorescein antibody. The two time points in a single cell were, first, the time of photobleaching fluorescein-tubulin, and second, the time of fixation. The pattern of fluorescence replacement in the bleached zone during this time interval revealed the relevant mechanisms. In fibroblasts, microtubule domains in the bleached zone are replaced microtubule by microtubule and not by mechanisms that affect all microtubules simultaneously. Of the models we consider, treadmilling and subunit exchange along the length do not account for this observation, but dynamic instability can since it suggests that growing and shrinking microtubules coexist. In addition, we show that the half-time for microtubule replacement is shortest at the leading edge. Dynamic instability accounts for this observation if in general microtubules do not catastrophically disassemble from the plus end, but instead have a significant probability of undergoing a transition to the growing phase before they depolymerize completely. This type of instability we call tempered rather than catastrophic because, through limited disassembly followed by regrowth, it will preferentially replace polymer domains at the ends of microtubules, thus accounting for the observation that the half-time of microtubule domain replacement is shorter with proximity to the leading edge.